Production of Bacterial Inoculants by Direct Fermentation on Nutrient-Supplemented Vermiculite - Graham-Weiss, Lori (1987)
When supplemented with a nutrient source and moisture, sterile finely ground vermiculite can be used to directly ferment bacterial cultures to prepare bacterial inoculants. All tested bacterial species, including Rhizobium japonicum, R. phaseoli, R. meliloti, R. leguminosarum, Bacillus megaterium, and several Pseudomonas strains, grew at least 10,000-fold in 1 week at room temperature. The final product was stable and had no special storage or handling requirements. Due to the unique properties of vermiculite, direct fermentation of bacteria on nutrient-supplemented vermiculite offers a reliable process for manufacturing bacterial inoculants.